2016
DOI: 10.1007/s11041-016-9932-8
|View full text |Cite
|
Sign up to set email alerts
|

Special Features of Electron-Beam Alloying of Replaceable Polyhedral Hard-Alloy Plates Under a Complex Surface Treatment

Abstract: Thermochemical treatment of a hard alloy is implemented by alloying its surface with the help of a low-energy strong-current electron beam prior to depositing a wear-resistant coating. The method increases substantially the service life of the tool. The laws of formation of refractory compounds in the surface layer due to initiation of a reaction of self-propagating high-temperature synthesis in the mode of thermal explosion are determined. The change in the wear behavior of the modified tools is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The experimental results demonstrated the feasibility of creating wear-resistant near-surface layers by electron-beam technology using a source of wide-aperture low-energy high-current electron beam (LEHCEB) [1]. Such layers were obtained by initiating exothermic chemical reactions between the substrate material and the film deposited on it with the formation of new phase components [2][3][4].…”
Section: Introductionmentioning
confidence: 93%
“…The experimental results demonstrated the feasibility of creating wear-resistant near-surface layers by electron-beam technology using a source of wide-aperture low-energy high-current electron beam (LEHCEB) [1]. Such layers were obtained by initiating exothermic chemical reactions between the substrate material and the film deposited on it with the formation of new phase components [2][3][4].…”
Section: Introductionmentioning
confidence: 93%
“…A separate scientific direction has been formed related to improving abrasive processing strategies, the characteristics of diamond tools, and optimizing diamond grinding modes to reduce roughness and increase crack resistance to solve the problem of minimizing defects in the surface layer of ceramic products [21][22][23][24]. One of the common approaches proposed by various researchers to reduce the defectiveness level in the surface layer formed on the surface of ceramics during diamond grinding is polishing as a finishing operation in the technological cycle of manufacturing ceramic products [25][26][27]. For example, the authors of this study demonstrated in a previous work that the use of additional finishing and polishing greatly reduces the index of defectiveness of the surface layer of samples made of Al 2 O 3 /TiC and SiAlON ceramics [28].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained using chemical and thermal methods of pretreatment. In this case, plasma nitriding [13][14][15], including ion-assisted nitriding [16,17], and surface alloying [18,19] are often used. It was found that such treatment improves the physicochemical characteristics of the substrate and its chemical affinity with the deposited material, as well as eliminates the sharp interface of separation between a relatively soft substrate and a hard coating.…”
Section: Introductionmentioning
confidence: 99%